2016
DOI: 10.1002/cbin.10700
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐34a modulates ErbB2 in breast cancer

Abstract: Breast cancer is the second highest cause of carcinoma-related death caused by distant metastasis in women. Estrogen receptor (ER), human epidermal growth factor receptor 2, (HER2) and progesterone receptor (PR) are three classified makers of breast cancer, which are defined as ER+, HER2+, and the most serious ER-PR-HER2- (triple-negative). It is well known that ErbB2 (V-Erb-B2 avian erythroblastic leukemia viral oncogene homolog 2) plays an important part in breast cancer. However, the molecular mechanisms un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 44 publications
0
12
0
2
Order By: Relevance
“…However, high miR-26a expression is associated with decreased expression of known cell cycle regulatory targets, including Cyclin E1, EZH2, and Cdk1, and positive clinical outcomes in patients with metastatic breast cancer taking tamoxifen [ 96 ]. Overexpression of the tumor suppressor miR-34a has also been reported to suppress ErbB2 expression and breast cancer cell growth and invasion [ 97 ]. Given the oncogenic function of ErbB2 in acquired tamoxifen resistance, miR-34a expression may be a prognostic target to predict tamoxifen responsiveness in ER + breast cancer patients.…”
Section: Mirnas and Drug Resistancementioning
confidence: 99%
“…However, high miR-26a expression is associated with decreased expression of known cell cycle regulatory targets, including Cyclin E1, EZH2, and Cdk1, and positive clinical outcomes in patients with metastatic breast cancer taking tamoxifen [ 96 ]. Overexpression of the tumor suppressor miR-34a has also been reported to suppress ErbB2 expression and breast cancer cell growth and invasion [ 97 ]. Given the oncogenic function of ErbB2 in acquired tamoxifen resistance, miR-34a expression may be a prognostic target to predict tamoxifen responsiveness in ER + breast cancer patients.…”
Section: Mirnas and Drug Resistancementioning
confidence: 99%
“…Fu et al found miR‐124 enhanced radiotherapy resistance in HER2‐positive breast cancer cells. Recently, Wang et al proved that miR‐24a could negatively regulate HER2 levels in breast cancer. Furthermore, miR‐495 has been reported abnormally expressed in many cancers and participated in cell proliferation, migration, and invasion .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the stratification analysis, we observed that the protective effect of rs11471161 in breast cancer was significant in ERBB2‐negative status (Table ). As the inhibition or knockdown of ERBB2 reduces proliferation and induces the apoptosis of breast cancer cells, it is reasonable to speculate that rs11471161 might interact with AC104135.3 and eventually influence breast cancer risk through ERBB2 signaling. In addition, we observed that breast cancer risk was also reduced in ER/PR‐positive women, women with a younger age at menarche, women with early age at first child‐birth, and premenopausal women.…”
Section: Discussionmentioning
confidence: 99%